Analysis Performance and Service Satisfaction of Transjakarta Bus Passengers Due to Changes in Routes (Case Study: Purpose of Pertamina Plumpang Stop Via PGC Early Route Toll - Plumpang Pertamina Becomes PGC - Cempaka Putih) - Tia Maharani (NAROTAMA UNIVERSITY, Indonesia)
Transjakarta served 189.77 million passengers in 2018 (Andapita, 2019). According to the Central Bureau of Statistics, the number of passengers increased by almost 31% in 2018. Corridor L 10a is one of the routes owned by Transjakarta with the initial route PGC 2 and the last stop at Tanjung Priok. Koridor L 10 has 8 stops and the total trip duration for this route is approximately 45 minutes (Transjakarta, 2019). This study aims to determine the performance of Transjakarta buses on route changes by referring to the data obtained in the COVID-19 pandemic condition and to determine the level of passenger satisfaction with changes in the Transjakarta L10a route. This research is a quantitative study using the state preference survey method. The survey was conducted by distributing questionnaires directly and google form which functions to collect data from passengers in the form of passenger performance and satisfaction with Transjakarta. The population in this study are customers or passengers of the new Transjakarta route L10a PGC 2 - Plumpang Pertamina. The sample selection method used was nonprobability sampling method with convenience sampling technique so that 110 respondents were obtained as samples. Data processing was performed using Excel and SPSS programs. The results of the research after analyzing the results data obtained through surveys and questionnaires, it can be concluded that satisfaction with Transjakarta bus services and fleets due to route changes is relatively high.